Extracellular green synthesis of chitosan-silver nanoparticles using Lactobacillus reuteri for antibacterial applications. (November 2020) - Tharani, Shanmugam; Bharathi, Devaraj; Ranjithkumar, R.
Abstract: In this work, we report the eco-friendly green synthesis of hybrid chitosan-silver nanoparticles (CS-AgNPs) using Lactobacillus reuteri ATCC 55730. The cell free extracellular biomass of L. reuteri was used as a reducing and capping agent for the synthesis of CS-AgNPs. The synthesized CS-AgNPs were characterized by using UV–visible spectroscopy, X-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy, and fourier transform infrared spectroscopy (FTIR). The formation of brown color and UV–visible absorbance peak ( λ max ) at 415 nm confirmed the synthesis of CS-AgNPs. XRD analysis revealed the face centred cubic crystalline structure of CS-AgNPs. FE-SEM analysis showed that the synthesized CS-AgNPs having quasi-spherical shaped nanostructure with an average size of 40–90 nm. The IR bands at 1465, 1543 and 1651 cm −1 indicated the presence of amine groups (-NH2 ), which confirmed the presence of CS in synthesized CS-AgNPs. The synthesized CS-AgNPs showed potential disc diffusion antibacterial activity against B. subtilis and E. coli pathogens. Furthermore, cotton fabrics impregnated with CS-AgNPs also showed bactericidal zone of inhibition against B. subtilis . Thus, the obtained results exposed that the synthesized CS-AgNPs using L. reuteri can be used against bacterial pathogens in textile industries. Graphical abstract: Image 1 Highlights: Chitosan-silver nanoparticles (CS-AgNPs) were synthesized using extracellular biomass of L. reuteri ATCC 55730. Green synthesized CS-AgNPs exhibited potential antibacterial activity. CS-AgNPs incorporated cotton fabric inhibited the growth of B. subtilis.